Appropriateness of empiric antimicrobial therapy with imipenem/colistin in severe septic patients: observational cohort study - Ahlem Trifi (Annals of Clinical Microbiology and Antimicrobials, 2018)
Abstract Background Empiric antimicrobial therapy (EAMT) using imipenem/colistin is commonly prescribed as a first line therapy in critically ill patients with severe sepsis. We aimed to assess the appropriateness of prescribing imipenem/colistin as EAMT in ICU patients. Methods A 3-year observational prospective study included ICU patients that required imipenem/colistin as EAMT. The EAMT was assessed according to microbiological and clinical outcomes. The outcomes were: delay in apyrexia, delay in the decrease of the biological inflammatory parameters (BIP), the requirement for vasoactive agents, bacteriological eradication, length of stay, ventilator days and 30-day mortality. Results 79 administrations of EAMT in 70 patients were studied. EAMT was appropriate in 52% of the studied cases. An ICU stay > 6 days was related to inappropriateness, and chronic respiratory failure was associated with appropriateness. In the appropriate EAMT group, we showed: earlier apyrexia, shorter delay in the decrease of the BIP and a reduced significant vasopressors requirement. Furthermore, EAMT improved survival with a median gain of 4 days. Inappropriate EAMT increased the mortality risk by six. The acquisition of NI in ICU was also an independent factor of mortality. Conclusions EAMT using imipenem-colistin was appropriate in half of the cases and inappropriateness was associated with an increased ICU mortality risk.